2015
DOI: 10.3892/or.2015.4325
|View full text |Cite
|
Sign up to set email alerts
|

Phloretin induces apoptosis of non-small cell lung carcinoma A549 cells via JNK1/2 and p38 MAPK pathways

Abstract: Phloretin (Ph) existing in apples, pears and various vegetables is known to have antitumor activities in several cancer cell lines. However, little is known about its effect on human lung cancer cells. The aim of the present study was to see whether Ph could induce apoptosis of non-small cell lung cancer (NSCLC) cells, and explore the possible underlying mechanism of action. We found that Ph markedly induced cell apoptosis of NSCLC cell line A549, and inhibited the migration of A549 cells in a dose-dependent m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
42
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 30 publications
1
42
0
Order By: Relevance
“…From western blot analyses there is a growing body of evidence indicating that phloretin increases the levels of the proteins p53, APAF-1 and DIABLO, and reduce the levels of XIAP protein to induce apoptosis. Previous studies combined with the results of the present study, have revealed that phloretin increases the levels of apoptosis of EC-109 cells via the mitochondria-apoptotic pathway (23)(24)(25).…”
Section: Discussionsupporting
confidence: 50%
“…From western blot analyses there is a growing body of evidence indicating that phloretin increases the levels of the proteins p53, APAF-1 and DIABLO, and reduce the levels of XIAP protein to induce apoptosis. Previous studies combined with the results of the present study, have revealed that phloretin increases the levels of apoptosis of EC-109 cells via the mitochondria-apoptotic pathway (23)(24)(25).…”
Section: Discussionsupporting
confidence: 50%
“…Especially, according to a study, Phloretin enhanced the anti-cancer ability of the human body [40]. Also, the research supported by the Key Program of the Shanghai Committee of Science and Technology [42] proves that Ph-induces apoptosis in NonSmall Cell Lung Cancer A549 cells [39].…”
Section: Discussionmentioning
confidence: 99%
“…However, Phloretin is the most sensitive drug for CCL than other three compounds, according to the results of 53 cell lines (59%). Phloretin (Ph) is a natural polyphenolic compound that exists in apples, pears as well as various vegetables are known to have anticancer activities in numerous cancer cell lines [40]. Ph has also been made known to have anticancer activities by "inducing apoptosis in human bladder cancer cells, leukemia cells, and human colon cancer cells, and inhibiting the growth, invasiveness, and migration of human liver cancer cells" [41].…”
Section: Discussionmentioning
confidence: 99%
“…22 Prostate and lung cancer are the most common cancer types worldwide and the PC-3 and A549 cell lines are used frequently as in vitro prostate and lung cancer model. 19,[23][24][25] We therefore, planned this study on the A549 and PC-3 cancer cell lines under in vitro conditions. Many in vitro assay are used for determination of antioxidant activity of herbal extracts and at least using two different methods are recommended.…”
Section: Discussionmentioning
confidence: 99%